1997
DOI: 10.1007/s11606-006-5049-x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse Among Homosexual Men: Prevalence and Association with Unsafe Sex

Abstract: Of 327 homosexual and bisexual men participating in an ongoing cohort study pertaining to risk factors for HIV infection who completed a survey regarding history of sexual abuse, 116 (35.5%) reported being sexually abused as children. Those abused were more likely to have more lifetime male partners, to report more childhood stress, to have lied in the past in order to have sex, and to have had unprotected receptive anal intercourse in the past 6 months (odds ratio 2.13; 95% confidence interval 1.15-3.95). Sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 14 publications
(15 reference statements)
4
31
0
3
Order By: Relevance
“…The reported prevalence of childhood sexual abuse among MSM in general has ranged from 11 to 37% (Doll et al 1992;Bartholow et al 1994;Lenderking et al 1997;Jinich et al 1998;Paul et al 2001;Traden et al 1999;Kalichman et al 2004), and a study conducted in Minneapolis/St. Paul found a 20% prevalence rate among African-Americans (Brennan et al 2007); however, the African-American sample size was too small to conduct meaningful significance tests.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of childhood sexual abuse among MSM in general has ranged from 11 to 37% (Doll et al 1992;Bartholow et al 1994;Lenderking et al 1997;Jinich et al 1998;Paul et al 2001;Traden et al 1999;Kalichman et al 2004), and a study conducted in Minneapolis/St. Paul found a 20% prevalence rate among African-Americans (Brennan et al 2007); however, the African-American sample size was too small to conduct meaningful significance tests.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,11,12 Not previously reported is the link between CSA and LSPs that appears to occur via PTSD, depression, and comorbid PTSD/depression. Findings revealed that this PTSD/depression linkage appears to be both moderating and mediating in nature, as characterized diagrammatically in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Further study of this sexual risk-taking group may ascertain variables that mediate and/or moderate the relationship between CSA and sexual risk behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Though the mechanisms involved are not yet entirely clear, there is mounting evidence that these associations between adverse childhood experiences and psychiatric risk are mediated by permanent effects of repeated stressors on HPA axis reactivity (Heim et al 2008;Pariante and Lightman 2008;Lupien et al 2009;Romeo 2010;Young and Korszun 2010). Several studies have shown elevated rates of childhood sexual abuse and risky family environment in nonheterosexuals (Cameron and Cameron 1995;Lenderking et al 1997;Fergusson et al 1999;Paul et al 2001;Tomeo et al 2001;Balsam et al 2005;Arreola et al 2008;Alanko et al 2009;Zietsch et al in press). A meta-analysis of studies examining the prevalence of childhood sexual abuse in nonheterosexuals (Rothman et al 2011) yielded higher rates than corresponding rates in a meta-analysis of studies of the general population (Stoltenborgh et al 2011).…”
Section: Adverse Childhood Experiences -Risky Family Environment and mentioning
confidence: 99%